Pumped storage hydropower in an abandoned open-pit coal mine: Slope stability analysis under different water levels - Liu, Feiyue; Yang, Ke; Yang, Tianhong; Gao, Yuan; Li, Jinduo; Liu, Qinjie; Fu, Qiang (Frontiers in Earth Science, 2022)
There are many coal mines being abandoned due to economic and environmental reasons in China. Repurpose of abandoned open-pit coal mines into pumped storage hydropower (PSH) can help with the storage of renewable energy, improve mine environment, and provide added economic values. Construction of PSH plant will change the water level of the abandoned pit which is envisaged as the lower reservoir, thus influencing the slope stability. In this paper, the Fushun west open-pit coal mine is taken as an example. Borehole investigation and tilt photogrammetry are used to obtain the rock mass quality and volume of the abandoned pit. Natural lake, dumps and another open-pit mine are envisaged as the upper reservoir, which can bring 40 MW, 3200 MW and 2000 MW electricity installed capacity, and -295 m, -200 m and -150 m water level in the lower reservoir. The numerical analysis software GeoStudio is used for slope stability analysis considering the hydraulic effect under different water level. Potential landslide risk may happen in several zone under specific water level. Further impervious and reinforcement work is needed to guarantee the slope stability for PSH plant construction in the Fushun west open-pit coal mine.